Mapping of neurokinin-like immunoreactivity in the human brainstem - Coveñas, Rafael (BioMed Central, 2003)
BACKGROUND: Using an indirect immunoperoxidase technique, we have studied the distribution of immunoreactive fibers and cell bodies containing neurokinin in the adult human brainstem with no prior history of neurological or psychiatric disease. RESULTS: Clusters of immunoreactive cell bodies and high densities of neurokinin-immunoreactive fibers were located in the periaqueductal gray, the dorsal motor nucleus of the vagus and in the reticular formation of the medulla, pons and mesencephalon. Moreover, immunoreactive cell bodies were found in the inferior colliculus, the raphe obscurus, the nucleus prepositus hypoglossi, and in the midline of the anterior medulla oblongata. In general, immunoreactive fibers containing neurokinin were observed throughout the whole brainstem. In addition to the nuclei mentioned above, the highest densities of such immunoreactive fibers were located in the spinal trigeminal nucleus, the lateral reticular nucleus, the nucleus of the solitary tract, the superior colliculus, the substantia nigra, the nucleus ambiguus, the gracile nucleus, the cuneate nucleus, the motor hypoglossal nucleus, the medial and superior vestibular nuclei, the nucleus prepositus hypoglossi and the interpeduncular nucleus. CONCLUSION: The widespread distribution of immunoreactive structures containing neurokinin in the human brainstem indicates that neurokinin might be involved in several physiological mechanisms, acting as a neurotransmitter and/or neuromodulator.